Limited genomic diversity and convergent adaptation of Brucella melitensis isolated from human in East China, from 2011 to 2024 - Huang, Lan; Zhou, Lu; Zhang, Nan; Zhou, Weizhong; Xu, Buyun; Hong, Jie; Zhang, Wei; Zhang, Ying; Xu, Ke; Bao, Changjun; Jiang, Hai; Tan, Zhongming; et al. (Frontiers in Microbiology, 2025)
ObjectiveThis study aimed to investigate the genomic epidemiology of Brucella melitensis in Jiangsu Province, a typical low-endemic region in East China where the incidence of human brucellosis has been increasing in recent years. Accordingly, a molecular epidemiological study was conducted on the 2,552 reported brucellosis patients in Jiangsu province, from 2011 to 2024.MethodsAll B. melitensis isolated from these patients were sequenced using next-generation sequencing (NGS), and 515 strains met the criteria for subsequent analysis. Core genome multi-locus sequence typing (cgMLST), pan-genome analysis and core genome single nucleotide polymorphism (cgSNP) were utilized to analyze genomic characteristics and establish the epidemiological linkages among global strains.ResultsAmong 515 isolates, 439 (85.24%) and 505 (98.06%) were identified as B. melitensis biovar 3 and sequence type 8(ST8), respectively. cgMLST further classified them into 28 core gene sequence types (cgSTs), including four novel genotypes (cgST1586-cgST1589) discovered in this study, whose identification expands the global cgMLST database and provides new markers for epidemiological surveillance. According to the cgSNP-based phylogenetic analysis, two distinct clades were persistently circulating within Jiangsu Province. One clade demonstrated significant genetic clustering with the Middle East strains, the other clade was closely linked to the hyper-endemic regions in China. Pan-genome analysis revealed their high homology, with core proteins primarily involved in amino acid transport and metabolism. Over the past 14 years, these isolates have exhibited limited genetic diversity and may be evolving toward a genotype that is better adapted to the host and environment.ConclusionThe human brucellosis in Jiangsu is mainly attributed to imported infections through various patterns, which is consistent with the typical epidemiology characteristics observed in low-endemic regions. The identification of four novel cgSTs and evidence of genomic evolutionary changes provide important insights to strengthen surveillance and guide targeted control strategies for brucellosis in East China.